2009
DOI: 10.2337/db08-1230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensive Therapy and Antecedent Hypoglycemia on Counterregulatory Responses to Hypoglycemia in Type 2 Diabetes

Abstract: OBJECTIVE-The physiology of counterregulatory responses during hypoglycemia in intensively treated type 2 diabetic subjects is largely unknown. Therefore, the specific aims of the study tested the hypothesis that 1) 6 months of intensive therapy to lower A1C Ͻ7.0% would blunt autonomic nervous system (ANS) responses to hypoglycemia, and 2) antecedent hypoglycemia will result in counterregulatory failure during subsequent hypoglycemia in patients with suboptimal and good glycemic control.RESEARCH DESIGN AND MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 38 publications
(31 reference statements)
0
57
0
2
Order By: Relevance
“…Recently, the counter-regulatory response to repetitive hypoglycaemia was investigated in intensive treatment of type 2 diabetes [24]. Repeated episodes of relatively mild hypoglycaemia reduced the counter-regulatory responses and impaired physiological defences against hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the counter-regulatory response to repetitive hypoglycaemia was investigated in intensive treatment of type 2 diabetes [24]. Repeated episodes of relatively mild hypoglycaemia reduced the counter-regulatory responses and impaired physiological defences against hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Often the symptoms are elusive and the outstanding manifestation is a mindboggling glucose instability with unexpected peaks at any time of the day and unexplained *Address correspondence to this author at the Diabetes and Endocrinology Unit -ASL RMH, Italy; Tel:+390693273094; Fax:+39063218855; E-mails: info@patriziotatti.it, tatti0@tin.it and unpredictable hypoglycemic episodes that impact on the life of the patient and his family [5]. Hypoglycemia is a serious limiting factor for the intensive treatment of hyperglycemia at any age [6,7]. Beyond its ravaging consequences GI neuropathy may be a marker of other neuropathies and diabetic complications.…”
Section: Pathophysiology and Symptomsmentioning
confidence: 99%
“…Davis et al reported equivalent reductions in adrenaline and symptomatic responses following antecedent hypoglycaemia as those seen in Type 1 diabetes. [22] Korzon-Borakowska et al [23] measured physiological responses before and after a period of tightening glycaemic control and demonstrated a lowering of the glycaemic thresholds for adrenaline and symptoms and a reduced adrenaline response. It therefore seems likely that tightening control might lead to a re-setting of protective physiological responses at a lower blood glucose.…”
Section: Effect Of Antecedent Hypoglycaemia In Type 2 Diabetesmentioning
confidence: 99%